Study on the reducibility of iron ore pellets at high temperature - Cao-Son Nguyen; Thanh-Hoan Nguyen; Son-Lam Nguyen; Anh-Hoa Bui (Vietnam Journal of Science, Technology and Engineering, 2022)
The behaviour of iron ore pellets in a blast furnace must be considered to improve ironmaking operations, especially when a large amount of the pellets is used. This study presents the reduction degree, mineralogical composition, and morphology of the pellet reduced in a gas mixture of 60% CO and 40% Ar at temperatures between 900 and 1,100oC. The pellet was prepared from iron ore from the Cao Bang province, Vietnam, by rotary drum. The obtained results showed that the reduction degree of the pellet increased with increasing reduction time and temperature. The activation energy of the reducing reaction was calculated to be 63.2 kJ/mol, which indicated that reduction occurred more easily in the present condition. X-ray diffraction (XRD) results revealed mineralogical phases such as hematite (Fe2O3), magnetite (Fe3O4), wüstite (FeO), metallic iron (Fe), and fayalite (Fe2SiO4) existing in the pellets when reduced for different times and temperatures. Fe and Fe2SiO4 were found to be the majority in the pellet that was reduced for 90 min at 1,100oC. Scanning electron microscopy (SEM) observations suggested the formation of a liquid phase, e.g., Fe2SiO4, which retarded the reducing reaction because it hindered the diffusion of gas flow inside the pellet. This phenomenon is essential to blast furnace ironmaking because pellets must be completely reduced before they move down to the liquid zone.